Innovative Methodology for Black Carbon Arctic Penetration Management - Valery M. ABRAMOV; Nickolay N. POPOV; Mikhail B. SHILIN; Arseny I. CHESTNOV; Alexandra L. ABRAMOVA; Konstantin S. PROSTAKEVICH; Elena A. PAVLOVA; Elena V. IVANOVA; Oksana V. PETRIEVA; Ekaterina A. RUMYANTSEVA (Communications of International Proceedings, 2021)
In paper, there are considered development results of innovative methodology for black carbon Arctic penetration management. This methodology is designed to demands of Industry 4.0 period and is adapted to conditions when while climate change and global economic shock because of Covid-19 pandemic. In studies, there are used methods of data bases constructing, web-technologies and virtual reality tools. Also, there are used Foresight technologies, theory of decision making under uncertainties and risk management. As digital tools in developed methodology, it is proposed to use digital online platforms, which integrate heterogeneous hardware and software resources with the use of web-technologies in distributed networks and wide application of cloud services. As a result of the research, a structural model is proposed as the basis for the developed innovative methodology. This model combines the investment objectives with cost of adequate managerial support for black carbon Arctic penetration management, adapted to climate change and Covid-19 pandemic. Platform https://www.researchgate.net/profile/Valery_Abramov2/ it is used for data exchange and preliminary discussion while study. Research was performed at the Russian State Hydrometeorological University within State Task of the Ministry of Science and Higher education of the Russian Federation, project FSZU-2020-0009.
Keywords: Black carbon; Arctic; climate change; Covid-19.